Brand Loyalty Is Influenced by the Activation of Political Orientations. Issue 3 (3rd July 2017) - Hoewe, Jennifer; Hatemi, Peter K.
Abstract : Using an experimental design that measures participants' actual behavior, this study tests the inclusion of a perceived outgroup in an advertisement for a well-established brand to determine if political orientations interact with an advertisement's content to predict consumption of that product. The results indicate that an advertisement's activation of one's political orientation can either change or reinforce brand loyalty. Specifically, more conservative individuals responded to the presence of Muslim and Arab individuals in a Coca-Cola advertisement by selecting Pepsi products despite their initial preference for Coca-Cola; whereas, more liberal individuals maintained their initial brand loyalty to Coca-Cola.